Learning Lotus 1-2-3 for Business - Krumm Rob (Addison-Wesley, 1988)
This book promotes the mastery of skills that are invaluable to students in their academic work and will be essential to them in the business and professional worlds. Learning Lotus 1-2-3, Formatting the Screen, Copies and Ranges, Absolute Vs. Relative, Using Disk Storage, Graphs, Data Management with 1-2-3, Advanced Data Functions, Working with Text, Financial Analysis, Lookup Tables, What is Processing, Conditional Functions, Trends and Matrices, Automating the Worksheet, 1-2-3 and Other Programs.